Peningkatan Kreativitas Seni Rupa Anak melalui Kegiatan Mencetak dengan Bahan Alam di TK Muslimat NU 02 Singorojo Kendal - Sarwono, Ridha; Artisa, Sari (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2022)
Children's artistic creativity in TK Muslimat NU 02 Singgorojo Kendal is still relatively low, this can be seen from the initial conditions that there are still many children who cannot make simple drawings, make simple drawings and redesign simple images. The method used by the teacher is not appropriate, not in accordance with the needs and development of the child and the media used by the teacher is not attractive to be one of the causes of this condition. This study aims to increase children's artistic creativity in making simple pictures, making simple pictures and simple picture redesign activities at TK Muslimat NU 02 Singorojo Kendal. This type of research is classroom action research, where the subject of this research is the students of TK Muslimat NU 02 Singorojo Kendal, totaling 20 people. The data in this study were obtained through observation, then the data was processed and analyzed using the percentage technique. The study was carried out for two cycles, the results obtained showed that printing with natural materials could increase the creativity of fine arts in Muslimat NU 02 Singorojo Kendal Kindergarten children. Before the study, children's art skills were still low, but after going through printing activities with natural materials it was seen that there was an increase in children's artistic creativity, therefore it was suggested to teachers to be more creative in using media and it was hoped that the school could prepare infrastructure to stimulate children's development through printing activities. with other natural ingredients.Keywords: artistic creativity, printing, natural materials